National workshop on the relationship between mangrove rehabilitation and coastal aquaculture in Vietnam, Hue City, 31 October - 2 November 1996 : Sponsored by action for mangrove reforestation (ACTMANG), Japan (Cres &Actmang, 1996)
Contents: The relationship between the mangrove ecosystem and aquaculture; techniques on planting tending and management mangroves; the socio-economic situation in mangrove areas.